Case Report: Recurrent psychotic episodes in the setting of non-COVID-19 upper respiratory viral infection - Atoui, Zahraa; Liu, Yi Ting; Lee, Andrew; Nardi, Caroline; Seery, Erin; Gwynette, McLeod Frampton (Frontiers in Psychiatry, 2025)
The viral hypothesis of schizophrenia suggests a link between viral respiratory infections and the development of psychotic symptoms. There have been several cases reporting development of new-onset psychosis after upper respiratory illnesses, including influenza and more recently coronavirus disease-2019 (COVID-19). Here, we present a case of a previously healthy African American female with no history of mental illness who developed psychotic symptoms following an upper respiratory illness in three distinct episodes at the ages of 16, 18, and 21. The patient had extensive medical workup during these episodes which did not identify an infectious source despite clear signs and symptoms of infection. Her psychiatric symptoms included disorganization, paranoia, response to internal stimuli and one episode with catatonic features. These symptoms improved with initiating antipsychotic treatment, and complete resolution was achieved within a couple months in the outpatient setting. In this report, we detail the disease course, medical workup, and selection of psychotropic treatments. This case highlights the challenges with identifying the diagnosis, completing appropriate workup, and selecting the best management for patients with similar presentations. It further demonstrates the connection between viral illnesses and development of psychosis and underscores the importance of further research to better understand patients with similar presentations.